The Role of Organic Matter in Improving Soil Physical Quality and Crop Production - YATNO, EDI (Jurnal Sumberdaya Lahan, 2011)
The presence of organic matter in soils is very important to maintain and improve a better soil physical quality so that the soils are able to support plant growth and yields. Organic matter plays an important role in the process of aggregate formation from primary soil particles. This paper aims to review the role of organic matter in improving soil physical quality and crop yields. The results of some studies indicate that addition of organic matter such as farmyard manure, composted sugarcane bagasse residue, and mulch from crop residues in different types of soils may decrease soil bulk density, increase aggregate stability, total porosity, soil water content, and crop yields. Farmyard manure and composted sugarcane bagasse residue have a greater effect on improvement of soil physical quality and crops production compared to mulch from crop residues. The decrease in soil organic matter contents may cause the decrease in soil physical quality so that the soil capability to support plant growth and yield is also decreasing.